5-2x+8=3(2x+3)

Simple and best practice solution for 5-2x+8=3(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2x+8=3(2x+3) equation:



5-2x+8=3(2x+3)
We move all terms to the left:
5-2x+8-(3(2x+3))=0
We add all the numbers together, and all the variables
-2x-(3(2x+3))+13=0
We calculate terms in parentheses: -(3(2x+3)), so:
3(2x+3)
We multiply parentheses
6x+9
Back to the equation:
-(6x+9)
We get rid of parentheses
-2x-6x-9+13=0
We add all the numbers together, and all the variables
-8x+4=0
We move all terms containing x to the left, all other terms to the right
-8x=-4
x=-4/-8
x=1/2

See similar equations:

| 8+8=-2(9x-8) | | 4x+1=8×+3 | | 12x²=17x-6 | | x²+12x=45 | | 2(k-5)=2k+5 | | (x^2-4)/x-2=2 | | (3m-5)+(-m+7)=0 | | 3(4p+5)=6(p-2) | | -5(5x+1)=10 | | x2+3x4-2x=7 | | 6.3x+3=4.8x-6 | | 3x+13=8x+23 | | 10u=3+9u | | -4x+12x+20=124 | | (x+4)/x-2=0 | | 8y+7=16 | | (2x+5)+(6x+5)=90 | | 2(8m-7)=(3+4m) | | 11r-2r+15=24 | | 3800=(12.57x)/12 | | 3(-4x-6)=18 | | (x-4)/4+6/(x+1)=5/4 | | -2q=3-q | | X-y=-21 | | 7x+10=15;x=2 | | 5c+3=23 | | 7x24=3x92 | | -4x+7=11-4x+7=11 | | 1/2n-2n/16=3/8 | | 3800=(3.1415926(4)x)/12 | | 11=4z-21 | | W=3-4m |

Equations solver categories